Chronic changes in plasma triglyceride levels do modify platelet membrane microviscosity in rats - Kunes, J; Devynck, M A; Zicha, J (Life sciences, 2000)
Lipid metabolism disorders were proposed to mediate numerous cell membrane alterations in various forms of hypertension. Elevated plasma triglycerides were found to be associated with changes in membrane structure and function related to altered microviscosity in particular domains of the cell membrane. The aim of our study was to determine if an abnormal triglyceride metabolism might play a causal role in these alterations of membrane dynamics. Using genetically hypertensive rats of the Prague hereditary hypertriglyceridemic (HTG) strain we investigated whether the elevation of circulating triglycerides induced by high fructose intake and/or their lowering by chronic gemfibrozil treatment (for 10 weeks starting at the age of 6 weeks) are followed by reciprocal changes in membrane microviscosity. Two different fluorescent probes exploring either the outer membrane leaflet (TMA-DPH anisotropy) or the membrane lipid core (DPH anisotropy) were used in platelets of HTG rats. DPH (diphenylhexatriene) fluorescence anisotropy was decreased in platelets of fructose-treated HTG animals with highly elevated plasma triglyceride levels, whereas it was increased in gemfibrozil-treated HTG rats in which triglyceride levels were almost normalized. On the contrary, TMA-DPH (trimethylamino-diphenylhexatriene) anisotropy was not substantially altered in platelets from HTG rats by the above modifications of circulating triglycerides. No changes of plasma cholesterol or blood pressure were associated with the triglyceride-dependent modifications of membrane core microviscosity. Our interventional study demonstrates a major causal role of circulating triglycerides in the control of the microviscosity of membrane lipid core.
Keywords: buněčná membrána; Cholesterol; Triglycerides; hypertriglyceridemie; cholesterol; Fluorescence Polarization; Rats, Inbred Lew; trombocyty; krysa rodu Rattus; zvířata; Hypertriglyceridemia; Blood Platelets; Blood Viscosity; triglyceridy; krevní tlak; viskozita krve; fluorescenční polarizace; Male; potkani inbrední LEW; Rats; Animals; Cell Membrane; mužské pohlaví; Blood Pressure